90t2 | ||
∑n=1∞xntn−100t=2t∑n=2∞xn−1tn−1− | ||
1−t |
90t2 | ||
∑n=1∞xntn−100t=2t∑n=1∞xntn− | ||
1−t |
90t2 | ||
(1−2t)∑n=1∞xntn=100t− | ||
1−t |
100t | 90t2 | |||
∑n=1∞xntn= | − | |||
1−2t | (1−t)(1−2t) |
100t | 90t((1−t)−(1−2t)) | |||
∑n=1∞xntn= | − | |||
1−2t | (1−t)(1−2t) |
100t | 90t | 90t | ||||
∑n=1∞xntn= | − | + | ||||
1−2t | 1−2t | 1−t |
2t | 90t | |||
∑n=1∞xntn=5 | + | |||
1−2t | 1−t |
5^2 | 52 |
2^{10} | 210 |
a_2 | a2 |
a_{25} | a25 |
p{2} | √2 |
p{81} | √81 |
Kliknij po więcej przykładów | |
---|---|
Twój nick | |